Long-term Neurological Outcome and Quality of Life after World Federation of Neurosurgical Societies Grades IV and V Aneurysmal Subarachnoid Hemorrhage in an Interdisciplinary Treatment Concept. Issue 6 (2nd February 2017) - Schwartz, Christoph; Pfefferkorn, Thomas; Ebrahimi, Caroline; Ottomeyer, Caroline; Fesl, Gunther; Bender, Andreas; Straube, Andreas; Pfister, Hans-Walter; Heck, Suzette; Tonn, Jörg-Christian; Schichor, Christian
Abstract: BACKGROUND: Detailed data on long-term functional outcome of patients with World Federation of Neurosurgical Societies (WFNS) grades IV and V aneurysmal subarachnoid hemorrhages (aSAH) are still scarce. OBJECTIVE: Assessment of long-term outcome of WFNS IV and V aSAH patients. METHODS: Functional outcome and quality of life were assessed by the modified Rankin scale (mRS) and the 36-item short-form health survey in consecutively treated aSAH WFNS IV and V patients between 2005 and 2010. Scores from the 36-item short-form health survey were compared to a healthy German population. Prognostic factors were analyzed by uni- and multivariate models. RESULTS: One hundred and seven eligible patients (median age: 53.0 years) were identified. After interdisciplinary consensus on optimal treatment, aneurysms were obliterated either by clipping (n = 35) or by coiling (n = 72). Ten patients were lost to long-term follow-up; the median clinical follow-up period was 3.2 years for the remaining 97 cases. Twenty-five of 97 died during the acute hospital phase and another 10 patients over the follow-up period leaving 62 long-term survivors. At the end of clinical follow-up, 40/97 patients, including 40/62 of long-term survivors, reached functional independence (mRS ≤ 2). Twelve of 97 patients were moderately (mRS = 3), 10/97 patients were severely disabled (mRS ≥ 4). Younger age (≤ 53 years; P = .001) and radiological absence of cerebral infarction ( P = .03) were the strongest predictors for favorable outcome. Quality of life was perceived to be only moderately reduced compared to the healthy control group. CONCLUSION: Poor-grade aSAH is not necessarily associated with poor long-term functional outcome; after aneurysm repair ∼60% of patients survived and among long-term survivors ∼ 60% regained functional independence.